Wear-resistant TPE composite yoga mat and preparation method thereof

CN122914601APending Publication Date: 2026-10-16GUANGDONG YUANHUA NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611086470.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,EVA是乙烯-醋酸乙酯无规共聚物,分子链以聚乙烯柔性链段为主,反复摩擦受力后分子链容易滑移、断裂,因此EVA对瑜伽垫耐磨和耐刮性能提升有限

Benefits of technology

本发明第一方面提供了一种耐磨TPE复合瑜伽垫,通过以SEBS作为基础弹性体,同时复配使用聚丙烯和TPEE,能够提升瑜伽垫的耐磨性能,使TPE发泡层在长期反复踩踏,拖拽的使用条件下,TPE发泡层的泡孔结构能够保持完整,不易塌陷,从而改善瑜伽垫起毛、掉屑的问题,使瑜伽垫的磨损失重能够显著降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914601A_ABST
    Figure CN122914601A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of yoga mats, and discloses a wear-resistant TPE composite yoga mat and a preparation method thereof. The wear-resistant TPE composite yoga mat comprises, from bottom to top, a rubber layer and a TPE foaming layer. The preparation raw materials of the TPE foaming layer comprise, by weight fraction, SEBS 45-50 parts, polypropylene 8-10 parts, mineral oil 10-12 parts, TPEE 5-6 parts, calcium carbonate powder 5-6 parts, SEBS-g-MAH 2-3 parts, foaming agent 0.8-1 part, crosslinking agent 0.5-1 part, zinc oxide 0.25-0.5 part, and stearic acid 0.2-0.5 part. The application uses SEBS as a basic elastomer, and simultaneously uses polypropylene and TPEE for compounding, so that the wear resistance of the yoga mat is improved, the cell structure of the TPE foaming layer can be kept intact and is not prone to collapse under the long-term repeated trampling and dragging use conditions, the problem of hairiness and chipping of the yoga mat is improved, and the wear loss of the yoga mat can be significantly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of yoga mat technology, and in particular to a wear-resistant TPE composite yoga mat and its preparation method. Background Technology

[0002] TPE yoga mats are fitness mats made from thermoplastic elastomers through extrusion foaming. The material is free of harmful substances such as PVC and plasticizers, and features lightweight, high resilience, flexibility, and recyclability. To ensure a non-slip surface, TPE yoga mats are often used in combination with a natural rubber backing.

[0003] To prevent TPE yoga mats from experiencing severe wear and tear over time, current technology incorporates EVA into the TPE foam layer to improve their abrasion and scratch resistance. However, EVA is a random copolymer of ethylene and ethyl acetate, with its molecular chains primarily composed of flexible polyethylene segments. Under repeated friction, these molecular chains are prone to slippage and breakage, thus limiting EVA's effectiveness in improving the abrasion and scratch resistance of yoga mats. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a wear-resistant TPE composite yoga mat and its preparation method, which aims to improve the wear resistance of the yoga mat.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention provides a wear-resistant TPE composite yoga mat, comprising, from bottom to top, a rubber layer and a TPE foam layer; the raw materials for preparing the TPE foam layer, by weight, include: 45-50 parts of SEBS, 8-10 parts of polypropylene, 10-12 parts of mineral oil, 5-6 parts of TPEE, 5-6 parts of calcium carbonate powder, 2-3 parts of SEBS-g-MAH, 0.8-1 part of foaming agent, 0.5-1 part of crosslinking agent, 0.25-0.5 parts of zinc oxide, and 0.2-0.5 parts of stearic acid.

[0006] In the wear-resistant TPE composite yoga mat, the SEBS is a mixture of YH-602T and YH-502T; the ratio of YH-602T and YH-502T by weight is 1:(1~2.5).

[0007] In the wear-resistant TPE composite yoga mat, the isotactic index of the polypropylene is ≥98%.

[0008] In the wear-resistant TPE composite yoga mat, the particle size range of the calcium carbonate powder is 60-90 nm.

[0009] In the aforementioned wear-resistant TPE composite yoga mat, the foaming agent is AC foaming agent; the mineral oil is at least one of naphthenic oil and white oil.

[0010] In the wear-resistant TPE composite yoga mat, the thickness of the TPE foam layer is 3-4 mm, and the thickness of the rubber layer is 1-2 mm.

[0011] In the aforementioned wear-resistant TPE composite yoga mat, the rubber layer is a natural rubber layer or a synthetic rubber layer.

[0012] A second aspect of this invention provides a method for preparing the aforementioned wear-resistant TPE composite yoga mat, comprising the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

[0013] In the preparation method of the wear-resistant TPE composite yoga mat, the temperature of the internal mixer in step S20 is 80-95℃; the temperature of the open mill is 90-100℃; and the temperature of the extruder is 90-110℃.

[0014] In the preparation method of the wear-resistant TPE composite yoga mat, the hot-press foaming in step S30 specifically involves heating and foaming in a hydraulic foaming machine at a temperature of 160-170°C for 25-35 minutes.

[0015] Beneficial effects: The first aspect of this invention provides a wear-resistant TPE composite yoga mat. By using SEBS as the base elastomer and compounding it with polypropylene and TPEE, the wear resistance of the yoga mat can be improved. Under long-term repeated stepping and dragging conditions, the cell structure of the TPE foam layer can remain intact and is not easy to collapse, thereby improving the problem of yoga mat pilling and shedding, and significantly reducing the wear and weight loss of the yoga mat.

[0016] The second aspect of this invention provides a method for preparing a wear-resistant TPE composite yoga mat. By pre-mixing and granulating SEBS, polypropylene, TPEE, SEBS-g-MAH, and mineral oil to obtain a wear-resistant masterbatch, the method allows the mineral oil to fully wet and swell the SEBS molecular chains and stably lock them within the gaps between the polymer chains. This avoids localized oil accumulation and oil migration during the subsequent mixing stage, preventing slippage and blooming on the finished yoga mat surface. Simultaneously, it enhances the interfacial bonding strength between the resin phases, preventing phase separation during subsequent mixing and foaming processes. This ensures that the TPEE wear-resistant modification component is uniformly dispersed throughout the TPE foam layer's cell walls, guaranteeing uniform and stable wear resistance across the entire TPE foam layer. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation process of the wear-resistant TPE composite yoga mat provided by the present invention.

[0018] Figure 2 This is a schematic diagram of the wear-resistant TPE composite yoga mat provided in Example 1.

[0019] Figure 3 This is a diagram showing the surface condition of the yoga mat after water droplets fall onto it in Example 1, a wear-resistant TPE composite yoga mat. Detailed Implementation

[0020] This invention provides a wear-resistant TPE composite yoga mat and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0021] The first aspect of this invention provides a wear-resistant TPE composite yoga mat, comprising, from bottom to top, a rubber layer and a TPE foam layer; the raw materials for preparing the TPE foam layer, by weight, include: 45-50 parts of SEBS, 8-10 parts of polypropylene, 10-12 parts of mineral oil, 5-6 parts of TPEE, 5-6 parts of calcium carbonate powder, 2-3 parts of SEBS-g-MAH, 0.8-1 part of foaming agent, 0.5-1 part of crosslinking agent, 0.25-0.5 parts of zinc oxide, and 0.2-0.5 parts of stearic acid.

[0022] In the raw materials used to prepare the TPE foam layer, SEBS, a hydrogenated styrene-butadiene-styrene block copolymer, is the basic elastomer of the TPE foam layer in this invention. The elastomer molecules have polystyrene hard segments at both ends and ethylene-butene soft segments in the middle. During friction, when external force deforms the cell walls of the TPE foam layer, the SEBS molecular chains can rapidly extend and store energy like a spring, and quickly retract after the external force is removed. This excellent resilience significantly reduces the material's compression set. After the yoga mat is stepped on for a long time, the cell structure can better maintain its integrity, is less prone to collapse, and avoids the problem of abrasive debris caused by cell structure damage, thus greatly improving the yoga mat's resistance to fatigue wear.

[0023] Meanwhile, thanks to the unique molecular structure of SEBS, after the blend system is melt-processed and cooled, the hard polystyrene segments in the molecular chain spontaneously aggregate to form nanoscale rigid micro-regions, which are uniformly dispersed in the continuous phase composed of ethylene butene soft segments. When the pad is subjected to reciprocating shear friction stress from dragging and stepping, the rigid styrene micro-regions can bear most of the friction load, preventing external forces from directly shearing and destroying the molecular chains of the middle soft segments, significantly reducing the probability of slippage and breakage of the soft segment molecular chains, and effectively alleviating problems such as friction fuzzing, chipping, and material wear loss. At the same time, the ethylene butene soft segments can buffer the locally concentrated frictional impact through their own elastic deformation, preventing the formation of microcracks in the cell walls of the TPE foam layer, preventing the continuous extension and expansion of cracks from the source, and further reducing the overall frictional loss of the foam layer.

[0024] Polypropylene, as the rigid component of the TPE foam layer, can form a rigid supporting phase within the elastic matrix, enhancing the shear strength and scratch resistance of the TPE foam layer surface. This reduces mass loss caused by reciprocating friction and improves the abrasion resistance of the yoga mat. Mineral oil, at least one of naphthenic oil and white oil, can swell the SEBS elastic matrix, reducing the overall material hardness and preventing the mat from being too hard or irritating to the skin. This meets the need for a soft yoga mat. Furthermore, mineral oil can reduce melt viscosity, improving the processing performance throughout the mixing, open milling, and extrusion processes. This ensures that the abrasion-resistant modified components and fillers are fully dispersed, preventing localized rapid wear caused by localized enrichment or deficiency of additives.

[0025] In the preparation of TPE foam layers, TPEE is a thermoplastic polyester elastomer. Its molecular backbone contains both rigid polyester hard segments and flexible polyether soft segments. The rigid polyester segments give the material excellent shear resistance and resistance to reciprocating friction. When blended, it can be evenly dispersed throughout the entire foam wall matrix of the foam layer, forming a wear-resistant reinforcing phase. This can significantly disperse the alternating shear stress caused by stepping and dragging, reducing the wear of the yoga mat. At the same time, the polyester segments can improve the tear resistance and fatigue resistance of the foam wall. After repeated rolling, stretching, and twisting, the foam mat is not prone to microcracks, damage, or through-cracks, and it can stably maintain the complete microporous structure of the foam layer, effectively extending the overall service life of the yoga mat.

[0026] SEBS-g-MAH is a maleic anhydride-grafted SEBS. One end of its molecular chain retains the SEBS chain segment structure, which can form good compatibility with SEBS, polypropylene, and TPEE, achieving a tight bond between the elastic phase and the rigid polyester phase. The maleic anhydride polar group at the other end can chemically bond with the hydroxyl groups on the surface of inorganic powders such as calcium carbonate powder and zinc oxide, significantly improving the interfacial bonding strength between inorganic fillers and organic polymer matrix. This effectively inhibits the agglomeration of calcium carbonate powder during the mixing process, preventing the filler from peeling off from the matrix and generating a large amount of wear debris under friction. At the same time, SEBS-g-MAH can eliminate phase separation defects in multi-component blend systems, ensuring that the TPEE wear-resistant modification component is uniformly dispersed throughout the foam layer wall, guaranteeing uniform and stable wear resistance performance throughout the foam layer.

[0027] To improve the processing flowability of the blend system while ensuring the abrasion resistance of the yoga mat, in a preferred embodiment, the SEBS is a mixture of YH-602T and YH-502T; the weight ratio of YH-602T to YH-502T is 1:(1~2.5). In this embodiment, YH-602T is a star-shaped SEBS, which can ensure the abrasion resistance of the yoga mat. However, its use alone or in excessive amounts will increase the viscosity of the overall melt of the blend system, increase the operating load of equipment in the mixing, open milling, and extrusion processes, and also cause processing defects such as uneven mixing and dispersion of the rubber compound, extrusion breakage, and whitening due to oil extrusion. YH-502T is a linear SEBS with well-defined and regular molecular chains, which can effectively reduce the overall melt viscosity of the blend system, reduce the equipment load during the mixing process, improve the dispersion uniformity of mineral oil, calcium carbonate powder, TPEE and other additives, and improve the smoothness of extrusion sheets. However, when linear SEBS is used alone, the melt strength is insufficient, and hot-pressing foaming is prone to problems such as bubble collapse, large and uneven cells, and weak wear resistance and deformation resistance. Therefore, this embodiment uses YH-602T and YH-502T in combination. By complementing the star-shaped SEBS and linear SEBS structures, the melt viscosity and melt strength of the system are balanced within a ratio range of 1:(1~2.5). The star-shaped SEBS maintains the excellent wear resistance and stable cell structure of the foam layer, while the linear SEBS optimizes the processing fluidity and reduces equipment energy consumption.

[0028] In a preferred embodiment, the polypropylene has an isotactic index ≥ 98%. Polypropylene with an isotactic index ≥ 98% has ultra-high regularity and can form high-density, high-rigidity crystalline microregions. These crystalline microregions can significantly improve the modulus of the foam wall and the surface scratch and abrasion resistance, disperse the shear stress generated by foot friction, thereby reducing the wear and weight loss of the TPE foam layer and improving the abrasion resistance of the yoga mat.

[0029] In a preferred embodiment, the calcium carbonate powder has a particle size range of 60–90 nm. Calcium carbonate powder within this particle size range has a high specific surface area, enabling it to embed itself in the molecular gaps of the elastomer and polypropylene, reinforcing the foam walls and improving the abrasion resistance of the yoga mat.

[0030] In a preferred embodiment, the foaming agent is an AC foaming agent. The AC foaming agent stably decomposes and releases nitrogen gas under hot and pressure conditions, which enables the mixture to expand and form a continuous microporous foam layer, giving the yoga mat cushioning, shock absorption, and lightweight properties; at the same time, the foaming ratio of the AC foaming agent is controllable, and the thickness of the TPE foam layer can be stably maintained at 3-4 mm, taking into account both rebound and surface wear resistance.

[0031] In a preferred embodiment, the crosslinking agent is bis-tert-butylperoxyisopropylbenzene. This crosslinking agent can decompose to generate free radicals during hot-pressing foaming, causing mild crosslinking of the SEBS molecular chains, improving melt viscoelasticity, locking in foaming gas, and preventing bubble wall rupture and collapse.

[0032] In order to balance the cushioning and rebound properties of the wear-resistant TPE composite yoga mat, as well as the wear-resistant and anti-slip properties of the surface, while controlling the overall hardness, weight and production cost of the composite yoga mat, in a preferred embodiment, the thickness of the TPE foam layer is 3-4 mm and the thickness of the rubber layer is 1-2 mm.

[0033] For example, the rubber layer may be a natural rubber layer or a synthetic rubber layer.

[0034] A second aspect of this invention provides a method for preparing the aforementioned wear-resistant TPE composite yoga mat, comprising the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

[0035] In the preparation method described above, the wear-resistant masterbatch is obtained by pre-mixing and granulating SEBS, polypropylene, TPEE, SEBS-g-MAH, and mineral oil. This allows the mineral oil to fully wet and swell the SEBS molecular chains and stably lock them within the gaps between the polymer chains, preventing localized oil accumulation, oil migration and precipitation during the subsequent mixing stage, and avoiding the problems of slippage and blooming on the surface of the finished yoga mat. Simultaneously, it improves the interfacial bonding strength between the resin phases, preventing phase separation during subsequent mixing and foaming processes, and ensuring that the TPEE wear-resistant modification component is uniformly dispersed throughout the foam wall of the entire foam layer, guaranteeing uniform and stable wear resistance throughout the TPE foam layer.

[0036] In the preparation method of the wear-resistant TPE composite yoga mat, the temperature of the internal mixer in step S20 is 80-95℃; the temperature of the open mill is 90-100℃; and the temperature of the extruder is 90-110℃.

[0037] To ensure the formation of uniform and fine pores in the foamed layer during the foaming process, the hot-press foaming in step S30 of the preparation method of the wear-resistant TPE composite yoga mat specifically involves heating in a hydraulic foaming machine at a temperature of 160-170℃ for 25-35 minutes. This foaming temperature range, combined with a holding time of 25-35 minutes, ensures that the cross-linking agent fully decomposes to generate free radicals, forming a moderately cross-linked network to enhance melt strength, effectively encapsulating the gas generated by the decomposition of the foaming agent to prevent pore rupture and collapse; simultaneously, it avoids the thermal degradation of SEBS molecular chains and the volatilization and seepage of mineral oil caused by prolonged high temperatures.

[0038] The following examples and comparative examples further illustrate the present invention. The sources of some of the raw materials used in the following examples and comparative examples are as follows.

[0039] YH-502T: Baling Petrochemical; YH-602T: Baling Petrochemical; Polypropylene (isotactic index ≥ 98%): Sinopec HC9006D Polypropylene (isotactic index 93%): Sinopec V30G Example 1 This embodiment provides a wear-resistant TPE composite yoga mat, which includes a rubber layer and a TPE foam layer from bottom to top. By weight, the raw materials for preparing the TPE foam layer include: 46.5 parts SEBS, 9 parts polypropylene (isotactic index ≥98%), 11 parts naphthenic oil, 5.5 parts TPEE, 5.5 parts calcium carbonate powder, 2.5 parts SEBS-g-MAH, 0.9 parts AC foaming agent, 0.7 parts crosslinking agent, 0.3 parts zinc oxide, and 0.3 parts stearic acid.

[0040] SEBS is a mixture of YH-602T and YH-502T. The ratio of YH-602T to YH-502T by weight is 1:2.

[0041] The calcium carbonate powder has a particle size range of 60–90 nm. The crosslinking agent is bis-tert-butylperoxyisopropylbenzene.

[0042] This embodiment also provides a method for preparing a wear-resistant TPE composite yoga mat, including the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

[0043] In step S20, the temperature of the internal mixer is 90°C; the temperature of the open mill is 95°C; and the temperature of the extruder is 100°C.

[0044] The hot-press foaming in step S30 specifically refers to foaming in a hydraulic foaming machine at a temperature of 165°C for 30 minutes.

[0045] Example 2 This embodiment provides a wear-resistant TPE composite yoga mat, which includes a rubber layer and a TPE foam layer from bottom to top. By weight, the raw materials for preparing the TPE foam layer include: 42 parts SEBS, 8 parts polypropylene (isotactic index ≥98%), 10 parts naphthenic oil, 5 parts TPEE, 5 parts calcium carbonate powder, 2 parts SEBS-g-MAH, 0.8 parts AC foaming agent, 0.5 parts crosslinking agent, 0.25 parts zinc oxide, and 0.2 parts stearic acid.

[0046] SEBS is a mixture of YH-602T and YH-502T. The ratio of YH-602T to YH-502T by weight is 1:2.5.

[0047] The calcium carbonate powder has a particle size range of 60–90 nm. The crosslinking agent is bis-tert-butylperoxyisopropylbenzene.

[0048] This embodiment also provides a method for preparing a wear-resistant TPE composite yoga mat, including the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

[0049] In step S20, the temperature of the internal mixer is 80°C; the temperature of the open mill is 90°C; and the temperature of the extruder is 90°C.

[0050] The hot-press foaming in step S30 specifically refers to foaming in a hydraulic foaming machine at a temperature of 160°C for 25 minutes.

[0051] Example 3 This embodiment provides a wear-resistant TPE composite yoga mat, which includes a rubber layer and a TPE foam layer from bottom to top. By weight, the raw materials for preparing the TPE foam layer include: 50 parts SEBS, 10 parts polypropylene (isotactic index ≥98%), 12 parts naphthenic oil, 6 parts TPEE, 6 parts calcium carbonate powder, 3 parts SEBS-g-MAH, 1 part AC foaming agent, 1 part crosslinking agent, 0.5 parts zinc oxide, and 0.5 parts stearic acid.

[0052] SEBS is a mixture of YH-602T and YH-502T. The ratio of YH-602T to YH-502T by weight is 1:1.

[0053] The calcium carbonate powder has a particle size range of 60–90 nm. The crosslinking agent is bis-tert-butylperoxyisopropylbenzene.

[0054] This embodiment also provides a method for preparing a wear-resistant TPE composite yoga mat, including the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

[0055] In step S20, the temperature of the internal mixer is 95°C; the temperature of the open mill is 100°C; and the temperature of the extruder is 110°C.

[0056] The hot-press foaming in step S30 specifically refers to foaming in a hydraulic foaming machine at a temperature of 170°C for 35 minutes.

[0057] Comparative Example 1 This comparative example provides a TPE composite yoga mat, which comprises a rubber layer and a TPE foam layer from bottom to top. The TPE foam layer differs from the TPE foam layer provided in Example 1 only in that the amount of YH-602T in SEBS is 13 parts and the amount of YH-502T is 35 parts.

[0058] This comparative example also provides a method for preparing a TPE composite yoga mat, which is the same as the method provided in Example 1.

[0059] Comparative Example 2 This comparative example provides a TPE composite yoga mat, which comprises a rubber layer and a TPE foam layer from bottom to top. The only difference between the TPE foam layer and the TPE foam layer provided in Example 1 is that polypropylene is not used in the raw materials for preparing the TPE foam layer.

[0060] This comparative example also provides a method for preparing a TPE composite yoga mat, which is the same as the method provided in Example 1.

[0061] Comparative Example 3 This comparative example provides a TPE composite yoga mat, which comprises a rubber layer and a TPE foam layer from bottom to top. The only difference between the TPE foam layer and the TPE foam layer provided in Example 1 is that the isotactic index of polypropylene in the raw material for preparing the TPE foam layer is 93%.

[0062] This comparative example also provides a method for preparing a TPE composite yoga mat, which is the same as the method provided in Example 1.

[0063] Comparative Example 4 This comparative example provides a TPE composite yoga mat, which comprises a rubber layer and a TPE foam layer from bottom to top. The only difference between the TPE foam layer and the TPE foam layer provided in Example 1 is that TPEE and SEBS-g-MAH are not used in the raw materials for preparing the TPE foam layer.

[0064] This comparative example also provides a method for preparing a TPE composite yoga mat, which is the same as the method provided in Example 1.

[0065] The sliding friction coefficient of the TPE composite yoga mat provided in the above embodiments was tested. The test was conducted according to the provisions of standard TY / T3802.1-2024 "Requirements and Test Methods for Fitness Yoga Equipment Part 1: Yoga Mats". The test results are shown in Table 1 below.

[0066] Table 1

[0067] As can be seen from the test results in Table 1, the wear-resistant TPE composite yoga mats provided in Examples 1-3 all meet the standard requirements and perform excellently in both dry and wet environments, indicating that the wear-resistant TPE composite yoga mats provided by the present invention combine wear resistance with excellent anti-slip performance.

[0068] Figure 3 The image shows the surface state of the yoga mat after water droplets fall onto it in Example 1. As can be seen from the image, the water droplets do not spread out on the yoga mat, indicating that the surface of the wear-resistant TPE composite yoga mat provided in Example 1 has certain hydrophobic properties, which can prevent sweat from penetrating into the interior of the yoga mat. Therefore, it can prevent the yoga mat from becoming moldy and improve the durability and hygiene of the yoga mat.

[0069] The abrasion resistance of the TPE composite yoga mats provided in the above embodiments and comparative examples was tested according to the provisions of standard GB / T 30314-2021 "Determination of abrasion resistance of rubber or plastic coated fabrics - Tuber method". The test results are shown in Table 2 below.

[0070] Table 2

[0071] As can be seen from the test results in Table 2, the wear mass loss provided by Examples 1-3 is consistently controlled at ≤0.06g / 1000 revolutions, which is better than the standard requirements. This indicates that the formulation system within the specified ratio range of the present invention can stably impart excellent wear resistance to the TPE composite yoga mat.

[0072] Comparing the wear mass loss data of Comparative Example 1 with that of Example 1, it was found that the wear resistance of the TPE composite yoga mat provided by Comparative Example 1 was not as good as that of the yoga mat in Example 1. This is because in the raw material system of the TPE foam layer of Comparative Example 1, the amount of star-shaped SEBS YH-602T decreased from 15.5 parts to 13 parts, and the amount of linear SEBS YH-502T increased from 31 parts to 35 parts. Although the increase in the amount of linear SEBS can improve the processing fluidity, star-shaped SEBS helps to improve the wear resistance of the TPE foam layer. Its significantly reduced proportion is not conducive to improving the wear resistance of the yoga mat.

[0073] Comparing the wear mass loss data of Comparative Example 2 with that of Example 1, it was found that the wear resistance of the TPE composite yoga mat provided by Comparative Example 2 was not as good as that of the yoga mat of Example 1. This is because polypropylene was not used in the raw material system of the TPE foam layer of Comparative Example 2.

[0074] Comparing the wear mass loss data of Comparative Example 3 with that of Example 1, it was found that the wear resistance of the TPE composite yoga mat provided by Comparative Example 3 was not as good as that of the yoga mat in Example 1. This is because Comparative Example 3 used polypropylene with a lower isotactic index. Polypropylene with an isotactic index of 93% has low molecular chain regularity and insufficient crystallinity, which weakens the effect of improving the wear resistance of the TPE foam layer.

[0075] Comparing the wear mass loss data of Comparative Example 4 with that of Example 1, it was found that the wear resistance of the TPE composite yoga mat provided by Comparative Example 4 was not as good as that of the yoga mat in Example 1. This is because TPEE was not used in the TPE foam layer raw material of Comparative Example 4, and the wear resistance strengthening effect of TPEE was lacking.

[0076] It is understood that those skilled in the art can make equivalent substitutions or modifications to the technical solution and inventive concept of the present invention, and all such substitutions or modifications should fall within the protection scope of the appended claims.

Claims

1. A wear-resistant TPE composite yoga mat, comprising, from bottom to top, a rubber layer and a TPE foam layer; characterized in that, The raw materials for preparing the TPE foam layer, by weight, include: 45-50 parts SEBS, 8-10 parts polypropylene, 10-12 parts mineral oil, 5-6 parts TPEE, 5-6 parts calcium carbonate powder, 2-3 parts SEBS-g-MAH, 0.8-1 part foaming agent, 0.5-1 part crosslinking agent, 0.25-0.5 parts zinc oxide, and 0.2-0.5 parts stearic acid.

2. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The SEBS is a mixture of YH-602T and YH-502T; the ratio of YH-602T and YH-502T by weight is 1:(1~2.5).

3. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The isotactic index of the polypropylene is ≥98%.

4. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The particle size range of the calcium carbonate powder is 60–90 nm.

5. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The foaming agent is AC foaming agent; the mineral oil is at least one of naphthenic oil and white oil.

6. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The thickness of the TPE foam layer is 3-4 mm, and the thickness of the rubber layer is 1-2 mm.

7. The wear-resistant TPE composite yoga mat according to claim 1, characterized in that, The rubber layer is a natural rubber layer or a synthetic rubber layer.

8. A method for preparing a wear-resistant TPE composite yoga mat as described in any one of claims 1-7, characterized in that, Includes the following steps: S10. Weigh SEBS, polypropylene, TPEE, SEBS-g-MAH and mineral oil according to the proportion, and then carry out mixing and granulation processes in sequence to obtain wear-resistant masterbatch. S20. The wear-resistant masterbatch, calcium carbonate powder, foaming agent, crosslinking agent, zinc oxide and stearic acid are mixed and plasticized in an internal mixer, then mixed and processed in an open mill, and finally placed in an extruder and formed into sheets through a die to obtain the mixture. S30. Place the mixture in a mold, hot-press and foam it to obtain a sheet; S40. The sheet is welded by a welding machine and then cut into sheets by a continuous sheet cutter to obtain a TPE foam layer. S50. The TPE foam layer and the rubber layer are laminated and embossed to obtain the wear-resistant TPE composite yoga mat.

9. The method for preparing the wear-resistant TPE composite yoga mat according to claim 8, characterized in that, In step S20, the temperature of the internal mixer is 80-95°C; the temperature of the open mill is 90-100°C; and the temperature of the extruder is 90-110°C.

10. The method for preparing the wear-resistant TPE composite yoga mat according to claim 8, characterized in that, In step S30, the hot-press foaming specifically refers to foaming in a hydraulic foaming machine at a temperature of 160-170°C for 25-35 minutes.